PEMBUATAN UNDANG-UNDANG DALAM PERSPEKTIF SIYASAH DUSTURIYAH - Begouvic, M. Eza Helyatha (Bahasa Indonesia, 2022)
Islam as a religion that has provided various normative and implementative frameworks, is used as a guide for human beings to behave on earth. Among Muslims there are also those who argue that Islam is a comprehensive religion, in which there is a political and constitutional system. Siyasah Duturiyah or science that regulates the authority of a country which is also part of Siyasa Fiqh, has a discussion of problems in state legislation. This will also be discussed between the concepts of the constitution (the constitution of the state and the history of the birth of legislation in a country), and legislation (how to formulate laws), as well as democratic institutions which are one of the important pillars of legislation. -invitation. This study also discusses the concept of the rule of law in the siyasa and the reciprocal relationship between the government and its citizens, as well as the rights of citizens that must be protected. The approach in this study is the Juridical Empirical Research Approach, where this research will take a juridical discussion, which is the object and main focus of researchers in viewing and analyzing the Making of Laws within the scope of Siyasah Duturiyah.